Effect of high carbondioxide pressure on some biochemical changes of longan 'Daw' fruit - K. Withee (2018)
Effect of high carbondioxide on pericarp polyphenol oxidase (PPO) activity, titrable acids (TA), pH and reducing sugars of the aril of longan cv. Daw fruit was study. The fruit were treated with high CO2pressure of 2 kg/cm2for 1 and 2 hr and non-treated. The treated and non-treated fruit were packed in foam trays, wrapped with PVC film and stored at 5°C, 85% RH for 24 days. The results showed that high CO2pressure also reduced PPO activity. However, TA and pH did not significant from the control. Reducing sugars tended to increased during the storage. The untreated fruit tended to have the highest reducing sugars content.